Moving Towards Sustainable Outcomes in Student Partnerships: Partnership Values in the Pilot Year - Marie, Jenny; McGowan, Susannah (International Journal for Students as Partners, 2017)
The UCL ChangeMakers scheme supports students and staff to work in partnership to enhance the University College London (UCL) learning experience. In 2014/15 we piloted the scheme with 10 projects run by 24 students in collaboration with 11 staff members. This paper will focus on our evaluation efforts of the pilot year through 4 illustrative case studies highlighting the successes and challenges of 4 projects. We focused our discussion on how projects were defined, what role students and staff should have had in defining the projects, and the sustainability of the projects once the student moves on or graduates. From our case study analysis, our findings revealed that a series of partnership values—collective responsibility, honesty, plurality, and trust—need to be considered in order to have an impact on the sustainability of the project and, more importantly, on the learning experience for students.